Circulation and Oxygen Distribution in the Tropical Atlantic Cruise No. 80, Leg 1; October 26 to November 23, 2009 Mindelo (Cape Verde) to Mindelo (Cape Verde) - Brandt, Peter; Brownell, D.; Dengler, Marcus; Didwischus, Sven-Helge; Fehsenfeld, Sandra; Fessler, Sebastian; Fischer, Jürgen; Funk, Andreas; Großkopf, Tobias; Hahn, Johannes; Halm, H.; Hormann, Verena; et al. (Leitstelle Deutsche Forschungsschiffe, Inst. f. Meereskunde, 2011)
METEOR cruise 80/1 was a contribution to the SFB 754 “Climate-Biogeochemistry Interactions in the Tropical Ocean”. Shipboard, glider and moored observations are used to study the temporal and spatial variability of physical and biogeochemical parameters within the oxygen minimum zone (OMZ) of the tropical North Atlantic. As part of the BMBF “Nordatlantik” project, it further focuses on the equatorial current system including the Equatorial Undercurrent (EUC) and intermediate currents below. During the cruise, hydrographic station observations were performed using a CTD/O2 rosette, including water sampling for salinity, oxygen, nutrients and other biogeochemical tracers. Underway current measurements were successfully carried out with the 75 kHz ADCP borrowed from R/V POSEIDON during the first part of the cruise, and R/V METEOR’s 38 kHz ADCP during the second part. During M80/1, an intensive mooring program was carried out with 8 mooring recoveries and 8 mooring deployments. Right at the beginning of the cruise, a multidisciplinary mooring near the Cape Verde Islands was recovered and redeployed. Within the framework of SFB 754, two moorings with CTD/O2 profilers were recovered and redeployed with other instrumentation in the center and at the southern rim of the OMZ of the tropical North Atlantic. The equatorial mooring array as part of BMBF “North Atlantic” project consists of 5 current meter moorings along 23°W between 2°S and 2°N. It is aimed at quantifying the variability of the thermocline water supply toward the equatorial cold tongue which develops east of 10°W during boreal summer. Several glider missions were performed during the cruise. One glider was recovered that was deployed two months earlier. Another glider was deployed for two short term missions, near the equator for about 8 days and near 8°N for one day. This glider was equipped with a new microstructure probe in addition to standard sensors, i.e. CTD/O2, chlorophyll and turbidity.